Developing Learning Media Based on E-Learning on Accounting Subject for Senior High School Students - Wardoyo, Cipto (Fakultas Ekonomi, Universitas Negeri Semarang, 2016)
This research aims to create the accounting learning media based on e-learning that uses Moodle software. It was one of e-learning applications which could be used in the learning activities and it was easy to be created. Â It was a Research and Development study which used Borg and Gall model. The stages of the research were: the initial needs analysis, the initial product development, the expert validation, the first revision; the limited field tests; the second revision; and the final product. The material validation was performed by the materials experts; whereas the media validation was performed the media experts and users (students). Findings show that there is 100% validated by the material experts and 96.67% by the media experts; 81.49% by the users (students), and thus the average validation was 92.72%. It means that the learning based on e-learning for accounting subject using Moodle application is very suitable in learning process. Thus; it is suggested to teachers to use the learning media based on e-learning.Â Then, facilities and infrastructure in the classroom should be provided in order to support the optimal utilization of the media.